Identification (GC and GC-MS) of unsaturated acetates in Elasmopalpus lignosellus and their biological activity (GC-EAD and EAG) - Jham, Gulab N.; Silva, Alexsandro A. da; Lima, Eraldo R.; Viana, Paulo (Journal of Separation Science, 2004)
Two insect colonies of Elasmopalpus lignosellus were reared in our laboratory, the first being initiated from pupae obtained from a cornfield in the region of Sete Lagoas, Minas Gerais and the second from a cornfield in the region of Goiânia, Goiás. From the two colonies, two extracts were prepared from the pheromone glands of virgin E. lignosellus females. The extract obtained from the first colony was designated as extract 1 while the extract obtained from the second colony was designated as extract 2. Extract 1 was analyzed by gas chromatography-mass spectrometry (GC-MS) with (Z)-9-hexadecenyl acetate [(Z)-9-HDA] and (Z)-11-hexadecenyl acetate [(Z)-11-HDA] being identified and confirmed by the formation of DMDS derivatives. In addition, a third acetate, which could be either (E)-8-hexadecenyl acetate [(E)-8-HDA] or (E)-9-hexadecenyl acetate [(E)-9-HDA] was detected by GC-MS. Extract 2 was analyzed by gas chromatography (GC) and gas chromatography-electroannetography (GC-EAD) revealing the presence of (Z)-11-HDA and (Z)-9-TDA. In addition, the same compounds elicited a response with the E. lignosellus male antenna obtained from the second insect colony. Electroantennography (EAG) screening with the male E. lignosellus antenna (obtained from the second insect colony) was conducted with the 23 possible tetradecenyl acetates (TDA) and 22 hexadecenyl acetates (HDA) as standards. Out of the 23 TDA isomers evaluated, only (Z)-9-TDA elicited a response and out of the 22 HDA [(Z) and (E) isomers gamma2 to delta13] evaluated only (Z)-11-HDA elicited a response. The acetate compositions of two extracts obtained from insects originating from the two states (Minas Gerais and Goiás) of Brazil were different from one another as well as from that obtained from insects in Tifton, GA, USA. The bioactivity data (GC-EAD) of the extract 2 differed from those reported for the Tifton, GA, USA population. These data suggest polymorphism in relation to the insect populations found in Brazil and in the USA. The possibility of the existence of an E. lignosellus sub-species cannot be ruled out.
Keywords: Elasmopalpus lignosellus; Acetates; Activity; Polymorphism; GC-MS; GC-EAD; EAG